Description of health behaviors in a group of university students from Lima - Becerra, Silvia (2016)
The present study aimed to analyze and describe the health behaviors or practices that of students in their first years of study at a private university in Lima. One hundred fifty five students participated with an average age of 18 years. A measure of health behaviors was administered anonymously. The results indicate that most students engage in healthy behaviors, but there are significant percentages of students who are presenting some risk behaviors, such little or no physical activity and exercise (especially in the group of womenand older students), little or no preventive health care, low consumption of water, fruits and vegetables, excessive alcohol consumption and excess use of tobacco. This study highlights the presence of symptomatic problems in sleep and leisure time in a large group of students. Intervention programs should be implemented in the university population to educate, motivate and change their adverse behaviors.